DEVELOPMENT OF ARTIFICIAL INTELLIGENCE-BASED EDUCATIONAL GAME MEDIA FOR SOCIAL SCIENCE LEARNING IN GRADE IV SDN 14 GEDONG TATAAN - Rizky Syahputra; Tuti Puspitasari (Jurnal TAM (Technology Acceptance Model), 2026)
This study aims to develop an Artificial Intelligence (AI)-based educational game for IPAS (Integrated Science and Social Studies) learning in fourth-grade students at SDN 14 Gedong Tataan and to evaluate its effectiveness in improving students’ learning outcomes and motivation. The research employed a Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The subjects consisted of 29 students and one teacher. Data were collected through observation, interviews, questionnaires, and tests (pre-test and post-test). The results showed that the developed media achieved an average questionnaire score of 4.39 (87.8%), categorized as very good, with a reliable instrument (Cronbach’s Alpha = 0.73). Furthermore, the N-Gain score of 0.625 indicated a moderate improvement in learning outcomes, and the t-test results showed a significant difference before and after using the media. Therefore, the AI-based educational game proved to be effective in enhancing students’ interest and learning outcomes in IPAS at the elementary school level.